Enzymatic production of functional oligosaccharides - A review - Fleuri, L. F. [UNESP]; Okino-Delgado, C. H. [UNESP]; Novelli, P. K. [UNESP]; Lima, G. P. P. [UNESP]; Pedrosa, V. A. [UNESP]; Francisco, V. B. [UNESP]; Andriolli, G. [UNESP]; Almendra, A. C. R. [UNESP] (Int Sugar Journal Ltd, 2014)
Interest in oligosaccharide production and its general characteristics is growing. The physiological effects resulting from its ingestion make them more attractive than its sweetness, and the versatility of these carbohydrates allows their use for human and animal nutrition, pharmacology and the cosmetics industry, among others. Several microorganisms are involved in enzyme production to create oligomers with biological activity, including fructooligosaccharides, galactooligosaccharides and aminoglucanoligosaccharides. Some oligomers are currently on the market, but the search for new microorganisms producing enzymes, high-yield processes for obtaining oligosaccharides, different physiological effects, and a correlation between chemical structure and function continues.
Keywords: prebiotics; beta-fructofuranosidase; beta-galactosidade; inulinase; chitinase